Command Decisions - Blumenson, Martin; Matloff, Maurice; Coakley, Robert W. [et al.]; Edited With Introduction Essay by Kent Roberts Greenfield (Rawalpindi Army Education Press)
An analysis of 23 decisions reached by chiefs of state and their military subordinates during World War II. Concerned with important political, strategic, tactical, and logistical questions, they include the invasions of North Africa and Normandy, the use of the atomic bomb, the capture of Rome, the campaigns in the western Pacific, and the internment of Japanese-Americans.
Include Index and Maps
Keywords: World War (1939-1945) -- Military campaigns